Copper‐Catalyzed Alkynylation of C(sp3)−H Bonds in N‐Fluoro‐sulfonamides. Issue 23 (15th October 2019) - Yin, Zhiping; Zhang, Youcan; Zhang, Shuo; Wu, Xiao‐Feng
Abstract: Herein, we developed a copper‐catalyzed approach for the remote C( sp 3 )−H alkynylation of N ‐fluoro‐sulfonamides. With Cu(OTf)2 as the catalyst, the carbon radical which generated from nitrogen radical‐mediated 1, 5‐hydrogen atom transfer, go through an addition/fragmentation reaction with various acetylene sulfones. A variety of internal alkynes were synthesized in high yield and regioselectivity. Notably, celecoxib‐derived substrate can also gave the corresponding functionalized product in good yield under the standard conditions. Abstract :